1998
DOI: 10.1164/ajrccm.158.1.9703005
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled Nitric Oxide (NO) Is Reduced Shortly after Bronchoconstriction to Direct and Indirect Stimuli in Asthma

Abstract: Exhaled NO is increased in patients with asthma and may reflect disease severity. We examined whether the level of exhaled NO is related to the degree of airway obstruction induced by direct and indirect stimuli in asthma. Therefore, we measured exhaled NO levels before and during recovery from histamine and hypertonic saline (HS) challenge (Protocol 1) or histamine, adenosine 5'-monophosphate (AMP), and isotonic saline (IS) challenge (Protocol 2) in 11 and in nine patients with mild to moderate asthma, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
75
1
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(84 citation statements)
references
References 18 publications
6
75
1
2
Order By: Relevance
“…The findings of this study support and extend published results on the effect of airway calibre on exhaled NO levels [7,11,12]. This study is the first to demonstrate the distinct relationship between FEV1 and exhaled NO levels in a cross-section of subjects with different airway diameters.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings of this study support and extend published results on the effect of airway calibre on exhaled NO levels [7,11,12]. This study is the first to demonstrate the distinct relationship between FEV1 and exhaled NO levels in a cross-section of subjects with different airway diameters.…”
Section: Discussionsupporting
confidence: 89%
“…However, the experiments in protocol 2 are very persuasive that it is indeed likely that airway diameter itself is important in this phenomenon. DE GOUW et al [11] who observed similar findings suggested that a decrease in surface area of the airways with bronchoconstriction might be responsible. The authors feel that this is less likely because the same number of epithelial cells will be present after bronchoconstriction although probably in a more convoluted formation.…”
Section: Discussionmentioning
confidence: 75%
“…During normal physiologic circumstances, the distal airways are known to narrow or collapse at the very last part of a forced expiration (16). This could in part cause the declining plateau seen at high flow rates, since airway narrowing will decrease the transit time resulting in reduced NO concentration, as seen during acute bronchoconstriction (17). Another explanation could be that it takes approximately 10 s for alveolar NO concentrations to reach steady state after inhalation (18,19), and this might influence exhaled NO levels significantly at high expiration flow rates when absolute NO levels are low.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested a possible impact of airway calibre reduction on the ability of FENO to capture asthma control. Several studies focusing on airway challenges have demonstrated that a reduction of airway calibre reduces FENO levels in the absence of any inflammatory changes [9][10][11][12]. This is most likely due to the decrease of available epithelial surface, which impairs NO diffusion from the airway epithelium into the airway lumen [13,14].…”
Section: Introductionmentioning
confidence: 99%